Cloud Data Protection Based On Crypto-Steganography Approach - Abdul Wahhab Hachim, Ethar (Newinera Publisher, 2024)
The benefits are numerous for organizations and people who work and learn using or through computers, some of these are scalability, affordability and availability of cloud computing services. However, one of the biggest issues still being faced in this area is that of security, especially concerning data privacy, thus limiting the use of such technologies. This paper seeks to address these concerns by developing a new approach to increasing protection of data in the cloud through development of Crypto-Steganography. The proposed method involves a two-tiered security mechanism: first, the presented data is protected with the use of advanced TWOFISH encipherment, which makes the data completely non-interpretated in case it gets to the hands of the unauthorized users. After that the encrypted data is then steganograghically inserted into a color image through least significant bit approach, where changes of the least significant bits of the image pixels will contain the encrypted data. Such double-layered approach does not only mask the presence of such sensitive information, but also ensures that even if there is an attempted invasion, such data can hardly be retrieved without the decryption passkey. The proposed approach of Crypto-Steganography is thoroughly tested through experiments and evaluation of distortion measures such as Weighted PSNR, UIQ; and C4 similarity measure. As seen in the results, the approach preserves low distortion and the wPSNR values are within the range of 45 – 50 dB, suggesting that the quality of the images is well preserved.